Manero Miguel, Fernando and García Cuesta, José Luis (coords.) (2016). Patrimonio cultural y desarrollo territorial. Cultural heritage and territorial development - Pallares-Barbera, Montserrat (Documents d’Anàlisi Geogràfica, 2019)
Manero Miguel, Fernando and García Cuesta, José Luis (coords.) (2016) Patrimonio cultural y desarrollo territorial. Cultural heritage and territorial development Pamplona: Thompson Reuters. Aranzadi, 415 p. ISBN 978-8490981009